Profitability of intercropping legumes with cereals: A farm-level analysis - Tzemi, Domna; Peltonen-Sainio, Pirjo; Palosuo, Taru; Rämö, Janne; Lehtonen, Heikki (Elsevier, 2025)
The benefits of grain legume and cereal intercropping, such as increased yield stability, resource efficiency, weed suppression, improved diversity of agricultural landscapes compared to monoculture systems have been extensively studied. Despite these benefits, the adoption of intercropping remains limited in Europe, including Finland, primarily due to socio-economic factors and perceived challenges. This research aims to fill the gap in understanding the farm-level economic implications of adopting oat-pea intercropping in Finnish agriculture. Using a dynamic optimization model, the study evaluates the profitability of oat-pea intercropping, considering dynamic factors such as crop yields, land utilization, and crop rotation, under different scenarios. Results showed that intercropping increases farmer's net present value (NPV) by reducing costs associated with nitrogen fertilization and increasing yields of various crops. When faba beans and peas are included as sole crops in the cropping system, profits increase by 37 %, driven by faba bean prices and positive yield effects on the following crops, i.e. pre-crop effects. Even with increased labor costs, including intercrops in crop rotations improves farm economy. More specifically, intercropping becomes unprofitable to be included in the crop rotation if labor costs increase by 2.6 times (442 €/ha). Increasing intercrops' price will lead to an increase in profits from 12 % to 32 %. Supportive policies, like enhancing agricultural extension services to train farmers in intercropping, could accelerate its adoption. Additionally, developing the market for pea-oat intercropping can promote wider acceptance by building strong connections between farmers, processors, and retailers.
Keywords: Finnish agriculture; farm management; dynamic optimization; pre-crop effects; yield; mixed crops